Fertility as a constraint on group size in African great apes - Dunbar, RIM (Oxford University Press, 2019)
Gorillas and chimpanzees live in social groups of very different size and structure. Here I test the hypothesis that this difference might reflect the way fertility maps onto group demography as it does in other Catarrhines. For both genera, birth rates and the number of surviving offspring per female are quadratic (or ∩-shaped) functions of the number of adult females in the group, and this is independent of environmental effects. The rate at which fertility declines ultimately imposes a constraint on the size of social groups that can be maintained in both taxa. The differences in group size between the two genera seem to reflect a contrast in the way females buffer themselves against this cost. Gorillas do this by using males as bodyguards, whereas chimpanzees exploit fission–fusion sociality to do so. The latter allows chimpanzees to live in much larger groups without paying a fertility cost (albeit at a cognitive cost).